KONTRIBUSI PEMBELAJARAN GEOGRAFI DAN LITERASI DIGITAL TERHADAP PERILAKU KERUANGAN DI SMA KOTA BANDUNG - Restu Anugrah Pribady, - (2023)
Globalization occurs as a result of interactions between humans and the environment which requires knowledge that is globally widespread and relevant. The city of Bandung is a fast-growing city, thus presenting a dynamic and diverse environment, with unique challenges and opportunities in terms of human interaction with its physical environment. Geography learning plays an important role in understanding geosphere phenomena related to globalization. In this context, geography teaches the importance of adapting to changes that occur by involving digital literacy. Digital literacy is very important amidst changes in the way humans interact with information and the surrounding environment. So, it is important to understand the impact of geography learning and digital literacy on the way students at Bandung City High Schools behave in space and the environment. This research aims to analyze the extent to which geography learning and digital literacy contribute to students' spatial behavior. The research sample of 385 people was selected using the purposive sampling method. Data were analyzed using the multiple linear regression method. The results of the analysis show that the Geography Learning variables (X1) and Digital Literacy (X2) together have an effect of 88.7% on the Spatial Behavior variable (Y). Furthermore, the results of the analysis show that Geography Learning has a positive influence of 51.7% on spatial behavior, while Digital Literacy has a positive influence of 61.1%. In addition, Geography Learning (X1) also contributed 79.6% to the variation observed in Digital Literacy (X2). Based on the calculation results, it can be concluded that geography learning and digital literacy both have a significant influence on students' spatial behavior with a score above 70%. Limitations in this study involve the generalization of the results only to the high school level and the methodological limitations of only using data from a questionnaire survey.